2021
DOI: 10.1021/acs.molpharmaceut.0c01177
|View full text |Cite
|
Sign up to set email alerts
|

99mTc-CN7DG: A Highly Expected SPECT Imaging Agent of Cancer with Satisfactory Tumor Uptake and Tumor-to-Nontarget Ratios

Abstract: A novel glucose derivative (CN7DG) possessing an isonitrile as a coordinating group was synthesized, and 99m Tc-CN7DG, which was expected to be a powerful tumor imaging agent for SPECT, was prepared in a kit by the reaction of CN7DG with SnCl 2 •2H 2 O and 99m TcO 4 − . 99m Tc-CN7DG exhibited good stability and was transported via glucose transporters. Biodistribution results in mice bearing A549 tumor models showed that 99m Tc-CN7DG had a higher uptake at the tumor sites and better tumor/blood and tumor/muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…2,3,5,6-Tetrafluorophenyl 6-isocyanohexanoate ( 4 ) and 2,3,5,6-tetrafluorophenyl 3-(2-isocyanoethoxy)propanoate ( 5 ) were synthesized according to the literature [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3,5,6-Tetrafluorophenyl 6-isocyanohexanoate ( 4 ) and 2,3,5,6-tetrafluorophenyl 3-(2-isocyanoethoxy)propanoate ( 5 ) were synthesized according to the literature [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Because the 99m Tc-labeled isocyanate-based complex had six isocyanate ligands which contain targeting group, its targeting ability to the target could be enhanced [ 16 , 17 , 18 ]. Recently, preclinical studies of 99m Tc-CN5DG and 99m Tc-CN7DG demonstrated that they could be promising candidates for tumor imaging [ 19 , 20 ]. The introduction of an ethylene glycol (PEG) chain can increase the hydrophilicity of the drug, thus improving its metabolic pathway in vivo [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…To seek novel 99m Tc-labeled glucose derivatives as tumor imaging agents, Zhang's group reported the synthesis and evaluation of a series of 99m Tc-labeled D-glucosamine derivatives with isonitrile as a coordinating group; among them, [ 99m Tc]Tc-CN7DG shows the highest tumor uptake and tumor-to-background ratios in the biodistribution and SPECT/CT studies in mice bearing A549 tumor xenografts [60]. [ 99m Tc]Tc-CN5DG could be readily prepared by using a CN5DG kit (Fig.…”
Section: Tc-labeled Glucose Derivativesmentioning
confidence: 99%
“…In 1958, the first heavy water reactor and the first accelerator were built and put into use in China at the China Institute of Atomic Energy (CIAE). The first batch of 33 radioisotopes including 24 Na, 32 P, 60 Co, and 131 I were successfully developed, thus initiating the undertakings of the production and application of radioisotopes and radiopharmaceuticals in China. Since the late 1950s, 131 I has been widely used in the diagnosis of thyroid function and radionuclide therapy for hyperthyroidism and thyroid cancer, and 32 P has been applied for the treatment of polycythemia vera and the control of cancerous pleural effusion and ascites, which pioneered the application of radioisotopes in clinical diagnosis and treatment in China.…”
Section: Introductionmentioning
confidence: 99%
“…However, SPECT scanners are installed in many hospitals around the world and, therefore, the use of tracers labeled with gamma-emitting nuclides for the imaging of hypermetabolic lesions might be a solution for these countries. Several glucose analogues have been preclinically evaluated for the SPECT imaging of tumor metabolisms [3][4][5][6][7], and [ 99m Tc]Tc-1-thio-D-glucose ([ 99m Tc]Tc-TG) is one Pharmaceutics 2022, 14, 1274 2 of 12 of such tracers (Figure 1). The mechanism of how [ 99m Tc]Tc-TG binds to malignant cells was elucidated using colorectal carcinoma (HCT-116) and human lung adenocarcinoma (A549) cells [4].…”
Section: Introductionmentioning
confidence: 99%